The Link Between Perception and Production in the Laryngeal Processes of Multilingual Speakers - Zsuzsanna Bárkányi; Zoltán G. Kiss (Languages)
The present paper investigates the link between perception and production in the laryngeal phonology of multilingual speakers, focusing on non-contrastive segments and the dynamic aspect of these processes. Fourteen L1 Hungarian, L2 English, and L3 Spanish advanced learners took part in the experiments. The production experiments examined the aspiration of voiceless stops in word-initial position, regressive voicing assimilation, and pre-sonorant voicing; the latter two processes were analyzed both word-internally and across word boundaries. The perception experiments aimed to find out whether learners notice the phonetic outputs of these processes and regard them as linguistically relevant. Our results showed that perception and production are not aligned. Accurate production is dependent on accurate perception, but accurate perception is not necessarily transferred into production. In laryngeal postlexical processes, the native language seems to play the primary role even for highly competent learners, but markedness might be relevant too. The novel findings of this study are that phonetic category formation seems to be easier than the acquisition of dynamic allophonic alternations and that metaphonological awareness is correlated with perception but not with production.